Downward particle fluxes, wind and a phytoplankton bloom over a polar continental shelf: A stormy impulse for the biological pump - Isla, Enrique; Gerdes, Dieter; Palanques, Albert; Gili, Josep Maria; Arntz, Wolf E.; König-Langlo, G. (Marine Geology, 2009)
14 pages, 15 figures, 1 table Downward particle fluxes were collected on two sites on the Antarctic continental shelf (407 m to 491 m depth) during 30 days in the austral spring and summer 2003–2004. The sampling period included the onset and demise of a phytoplankton bloom and the occurrence of a storm. The calm period previous to the storm enabled the phytoplankton to flourish and set conditions for a bloom. The storm enhanced mixing, production and particle aggregation that increased the transport of organic matter to the seabed. The windinduced particle pulse represented 53% (306 mg OC m−2 and 826 mg bSi m−2) of the total mass flux collected during the study period at midwater column (179 m depth). Close to the seabed (28 m above the seafloor)the sample corresponding to the period of the highest flux in the upper trap was lost; however, high OC and bSi fluxes (279 mg OC m−2 and 901 mg bSi m−2) were still collected three days after. These fluxes were 42% and 30% of the respective fluxes collected at this depth throughout the study. Diatom aggregates and faecal pellets were the main vehicles for the transport of organic matter. Faecal pellets and foraminifera tests were ubiquitous in the traps; however, ellipsoidal faecal pellets were only present in the deeper traps where in some periods were more abundant than the faecal strings. Comparatively smaller particle fluxes than in other Antarctic settings during the same season were found and the differences attributed to the denser sea ice coverage (N60%) observed during the present study. The chemical quality and the magnitude of the particle fluxes suggest that the phytoplankton bloom and the storm developed at least over a 75 km long area. The coincidence of these events produced in three days organic carbon and biogenic silica pulses over an area of at least 805 km2 of the continental shelf that may have amounted 85 to 225 tons and 308 to 725 tons, respectively. The occurrence of storms (N15 m s−1) during the spring–summer season in the last 20 years ...